New xanthine derivative B-YR-2 as antioxidant modulator of post-stroke damage of sensorimotor cortex neurons in rats - Belenichev, I. F.; Aleksandrova, K. V.; Nosach, S. F.; Levich, S. V.; Yurchenko, D. M.; Abramov, A. V.; Buchtiyarova, N. V.; Suprun, E. V.; Бєленічев, Ігор Федорович; Александрова, Катерина Вячеславівна; Носач, Світлана Григорівна; Юрченко, Дар'я Миколаївна; et al. (India : Tamilnadu State, 2014)
Acute ischemic stroke is a major cause of long-term disability and the second leading cause of mortality worldwide. One of main parts of it pathogenesis is production of reactive oxygen species. The goal of this study was to evaluate the neuroprotective effect of the new xanthine derivative B-YR-2 (hydrazide of 1,3-dimethyl-8 Nbenzylaminoxanthinyl-7-acetic acid), which demonstrated high antioxidant qualities in vitro, in comparison with thiotriazoline, mexidol and citicoline. Injection of B-YR-2 compound to the rats with experimental stroke had the most pronounced neuroprotective effect. B-YR-2 increased number of glial cells and neurons in the cerebral cortex and stimulated their morphofunctional activity.
Keywords: ischemic stroke; antioxidants; xanthine derivatives; neuroprotection; cerebroprotective action; frontal cortex